Development and performance evaluation of an ultra precision ELID grinding machine - Saleh, Tanveer; Rahman, M. Sazedur; Lim, H.S.; Rahman, M. (Elsevier, 2007)
ELID grinding is drawing more and more attention by the researchers for its smart method of in-process dressing of the grinding wheel. A number of studies have been done by many people to investigate the mechanism and application of the process, though no significant effort has been made so far to develop an intelligent machinetool especially dedicated for ELID grinding. This paper aims to present the development and performance evaluation of an ultra precision intelligent ELID grinding machine. The machine is a five-axis machine, which includes three conventional linear axes (X, Y and Z) and a spindle axis. On top, another rotational axis has been included to assist the aspheric/spherical lens grinding. In order to introduce intelligence to the machine two on machine measuring system have been developed and incorporated. Experiments have been carried out on BK7 optical glass for evaluating the performance of the machine. A nano-level surface finish has been achieved, using #4000 series wheel.